Development of E-Book Teaching Materials about the Four Days Battle in Surakarta August 7-10, 1949 as a Source of Local History Learning for History Education Students - Ivan Prapanca Wardhana; Leo Agung Sutimin; Susanto Susanto (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
An e-Book is a book that is displayed in digital form that can be used as a support for the learning process. This development aims to develop a digital book (e-Book) about the Four-Days Battle in Surakarta August 7-10, 1949 as a source of local history learning for students of the history education study program. This study uses the Research and Development (R&D) method in its research procedures and uses the ADDIE development procedure (Analysis, Design, Development, Implementation, Evaluation) as the stage of developing teaching materials. This product involves two media validators, two material validators, lecturers, and students of history education at the Veteran Bangun Nusantara University. The results of this development show that the e-Book based on the Four-Days Battle in Surakarta is proven to be valid and feasible based on the assessment of media and material factors from experts. Meanwhile, the results of assessments from small, large, and broad groups also show the effectiveness of the product based on the analysis. needs.